2019
DOI: 10.3389/fnins.2019.00253
|View full text |Cite
|
Sign up to set email alerts
|

Intradural Spinal Cord Stimulation: Performance Modeling of a New Modality

Abstract: Introduction: Intradural spinal cord stimulation (SCS) may offer significant therapeutic benefits for those with intractable axial and extremity pain, visceral pain, spasticity, autonomic dysfunction and related disorders. A novel intradural electrical stimulation device, limited by the boundaries of the thecal sac, CSF and spinal cord was developed to test this hypothesis. In order to optimize device function, we have explored finite element modeling (FEM).Methods: COMSOL®Multiphysics Electrical Currents was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…HMs have been extensively used in the context of spinal cord stimulation [8][9][10][11] , deep brain stimulation [12][13][14][15] and peripheral nerve stimulation (PNS). This tutorial specifically addresses peripheral neural interfaces that directly contact the nerve to be stimulated: the general framework can be easily adapted to different applications (for example, transcutaneous stimulation 16 ).…”
Section: Hybrid Modelingmentioning
confidence: 99%
“…HMs have been extensively used in the context of spinal cord stimulation [8][9][10][11] , deep brain stimulation [12][13][14][15] and peripheral nerve stimulation (PNS). This tutorial specifically addresses peripheral neural interfaces that directly contact the nerve to be stimulated: the general framework can be easily adapted to different applications (for example, transcutaneous stimulation 16 ).…”
Section: Hybrid Modelingmentioning
confidence: 99%
“…To evaluate other types of motor units, such as fast fatigable motor units, the stimulation waveforms estimated in this study should be adjusted considering the discrepancy in electrical and mechanical properties, particularly in regard to the somatic input resistance, system time constant, rheobase current, afterhyperpolarization potential, and PIC dynamics in spinal motoneurons ( Lee and Heckman, 1999 ; Heckman and Enoka, 2012 ), twitch rate and amplitude, progressive force reduction phenomenon (i.e., the sag observed over short contraction time <2 s and fatigue over a long contraction time >2 min), and length– and velocity–tension properties of muscle fibers ( Brown et al, 1999 ; Burke, 2011 ). Fourth, the present study did not consider the shape of the current pulse ( Anderson et al, 2019 ). Thus, the waveforms predicted in the current study might vary according to the shape of the current pulse.…”
Section: Discussionmentioning
confidence: 99%
“…At its origins as a therapy, virtually all SCS was carried out by intradural implantation of the electrodes (65), but with the more minimally invasive epidural approaches eventually becoming the standard of care. Even so, recent work has now shown that significant improvements in selectivity of stimulation targets within the spinal cord might be achieved with intradural arrays (66,67), and efforts to develop clinically useful devices are underway (68,69). The ability to implant SCS devices intradurally suggests the unique opportunity of collateral CSF assay at the time of implantation for the purpose of optimizing the therapeutic strategies, via evaluation of several types of biomarkers such as those discussed in the "Chemically Sensing-Metabolites, Neurotransmitters, and Inflammatory Markers" section.…”
Section: Optimizations For Intradural Stimulationmentioning
confidence: 99%